Celiac disease diagnosis from videocapsule endoscopy images with residual learning and deep feature extraction. (April 2020) - Wang, Xinle; Qian, Haiyang; Ciaccio, Edward J.; Lewis, Suzanne K.; Bhagat, Govind; Green, Peter H.; Xu, Shenghao; Huang, Liang; Gao, Rongke; Liu, Yu
Highlights: A novel block wise feature recalibrate module merged into CNN-based networks for CD recognition. Squeeze and excitation block with channel recalibration is firstly applied to adaptively recalibrate the feature of CD image. The combination of ResNet50 with the SVM classifier can be useful to measure discriminative and subtle villous atrophy in CD. Abstract: Background and Objective: Videocapsule endoscopy (VCE) is a relatively new technique for evaluating the presence of villous atrophy in celiac disease patients. The diagnostic analysis of video frames is currently time-consuming and tedious. Recently, computer-aided diagnosis (CAD) systems have become an attractive research area for diagnosing celiac disease. However, the images captured from VCE are susceptible to alterations in light illumination, rotation direction, and intestinal secretions. Moreover, textural features of the mucosal villi obtained by VCE are difficult to characterize and extract. This work aims to find a novel deep learning feature learning module to assist in the diagnosis of celiac disease. Methods: In this manuscript, we propose a novel deep learning recalibration module which shows significant gain in diagnosing celiac disease. In this recalibration module, the block-wise recalibration component is newly employed to capture the most salient feature in the local channel feature map. This learning module was embedded into ResNet50, Inception-v3 to diagnose celiac disease using a 10-time 10-fold cross-validation based upon analysis of VCE images. In addition, we employed model weights to extract feature points from training and test samples before the last fully connected layer, and then input to a support vector machine (SVM), k-nearest neighbor (KNN), and linear discriminant analysis (LDA) for differentiating celiac disease images from heathy controls. Results: Overall, the accuracy, sensitivity and specificity of the 10-time 10-fold cross-validation were 95.94%, 97.20% and 95.63%, respectively. Conclusions: A novel deep learning recalibration module, with global response and local salient factors is proposed, and it has a high potential for utilizing deep learning networks to diagnose celiac disease using VCE images. Graphical abstract: Image, graphical abstract